2017
DOI: 10.1038/srep43691
|View full text |Cite
|
Sign up to set email alerts
|

NEDDylation of PB2 Reduces Its Stability and Blocks the Replication of Influenza A Virus

Abstract: Post-translational modifications of viral proteins play important roles in regulating viral replication. Here we demonstrated that the PB2 of influenza A virus (IAV) can be modified by NEDD8. We revealed that E3 ligase HDM2 can promote PB2 NEDDylation. Overexpression of either NEDD8 or HDM2 can inhibit IAV replication, while knockdown of HDM2 has the opposite effect. Then we identified residue K699 in PB2 as the major NEDDylation site. We found that NEDDylation deficient PB2 mutant (PB2 K699R) has a longer hal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 46 publications
3
38
0
Order By: Relevance
“…However, in these studies the researchers did not find that any viral protein from KSHV and HIV had been NEDDylated. Recently, we showed that PB2 of influenza A virus can be NEDDylated, which inhibits viral replication (33). In the present study, we showed that neurodegenerative disorders, and cardiac disease (34).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…However, in these studies the researchers did not find that any viral protein from KSHV and HIV had been NEDDylated. Recently, we showed that PB2 of influenza A virus can be NEDDylated, which inhibits viral replication (33). In the present study, we showed that neurodegenerative disorders, and cardiac disease (34).…”
Section: Discussionmentioning
confidence: 65%
“…It has been reported that NEDDylation plays important roles in viral pathogenesis (31)(32)(33). For example, Hughes et al demonstrated that NEDDylation is required for Kaposi's sarcoma-associated herpesvirus (KSHV) to replicate its genome and essential for the viability of KSHV-infected lymphoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Fehr et al found that mutation of the macrodomain of nsp3, important for countering ADP-ribosylation, resulted in virus attenuation [ 109 ], while another report demonstrated that binding of the methyl donor S-adenosyl- l -methionine (SAM) to 2′-O-methyltransferase nsp16 enhanced MERS-CoV replication, promoting the recruitment of the allosteric activator nsp10 [ 110 ]. On the other hand, IAV induced host histone deacetylase 1 dysregulation in lung epithelial cells, inhibiting IAV infection [ 111 ] while NEDDylation (conjugation of a ubiquitin-like protein, neural precursor cell expressed developmentally down-regulated 8 (NEDD8)) of PB2 protein reduced its stability, suppressing IAV replication [ 112 ]. Nevertheless, the role of epigenetic modification during respiratory virus infection is not well understood; the application of phosphoproteomics to characterization of the human macrophage response to IAV infection [ 113 ] serves as a model for future studies.…”
Section: Modulation Of Immune Responses Against Respiratory Virus Infmentioning
confidence: 99%
“…ADP-ribosylation promotes their ubiquitination and subsequent degradation, providing another example of PTM cross-talk. In an apparent paradox, neddylation of PB2 blocks viral replication [ 17 ], yet inhibition of the neddylation pathway also results in poor replication [ 18 ]. In sum, RNP PTMs serve both as tunable ways to regulate polymerase function and as antiviral responses that attempt to block replication.…”
Section: Introductionmentioning
confidence: 99%